Health-Related Quality of Life in Chronic Renal Predialysis Patients Exposed to a Prevention Program - Medellín, 2007-2008 - Delgado, Carlos E. Yepes; Jaramillo, Yanett M. Montoya; Orozco, Beatriz E. Orrego; Acevedo, Daniel C. Aguirre (IntechOpen, 2012)
None